Influência de baixas temperaturas sobre aspectos bionômicos de Musca domestica (Linnaeus, 1758) (Diptera, Muscidae) e Chrysomya megacephala (Fabricius, 1794) (Diptera, Calliphoridae) - Rosenthal, Luciane D'avila (2012)
Survival, longevity and reproductive aspects of the flies are related to biotic, abiotic and interaction between them. The temperature, for example, directly influences the speed and rate of development, behavior, feeding, fecundity, dispersal, reproductive potential and the number of individuals in a population. Given this, the objective of this study was to determine the influence of storage muscoidea adults of Musca domestica and Chrysomya megacephala at low temperatures (5 and 10°C) through the analysis of the bionomic survival, longevity, number of ovos.fêmeas-1 and viability (%) eggs. The experiment was conducted at the Laboratory of Insect Biology, Federal University of Pelotas, and the achievement were maintained colonies of both species, pre-established laboratory conditions (temperature 25+2°C, relative humidity 70+10%; photoperiod of 12 hours). We randomly selected 15 pairs/species/repeat, and packaged in glass bottles, with three replicates/treatment. All repetitions were simultaneously placed in a chamber of biological development (B.O.D.) at temperatures of 5, 10 and 25+2°C (control) and is the factor A (temperature controlled conditioning of adults). The flies were removed from B.O.Ds. 7, 14, 21, 28, 35 and 42 days, constituting Factor B (exposure time of adult B.O.D.), proceeding in the measurement cages and packaging, the survivors of the respective temperature of 25+2°C, to the death of the last diptera, analyzing longevity, the average number of ovos.fêmeas-1 and viability (%) eggs. The results were statistically analyzed with the purpose of observing whether each temperature controlled conditioning of adults was limiting within each exposure time of adults in B.O.D. Thus we can infer that the use of low temperatures (5 and 10°C), in order to reduce metabolic rates and the development of these insects in adulthood, was a strategy that interfered on bionomic aspects analyzed for the two species under study. In conclusion: The temperature controlled exposure of adults 5°C prevents the creation of C. megacephala; The utilization of low temperature conditioning (5 and 10ºC) is a strategy that impacts negatively on the survival of adults (males + females), female survival, male survival, longevity, the average number of ovos.fêmeas- 1 and viability of eggs of M. domestica and C. megacephala when compared to a temperature of 25+2°C. The time of exposure of adult M. domestica and C. megacephala in B.O.D. for 7 days, allows the occurrence of overall survival (females + males), female survival, male survival, longevity, higher average number of ovos.fêmeas-1 and egg viability; The number of adult female survivors of M. domestica exposed to low temperatures conditioning (5 and 10°C) is numerically more significant, the number of male survivors.